Complex Systems Theory and Development Practice: Understanding Non-lin ear Realities - Rihani, Samir (Zed Books, 2002)
Here, for the first time, development studies encounters the set of id eas popularly known as 'Chaos Theory'. Samir Rihani applies to the pro cesses of economic development, ideas from complex adaptive systems li ke uncertainty, complexity, and unpredictability. Rihani examines vari ous aspects of the development process - including the World Bank, deb t, and the struggle against poverty - and demonstrates the limitations of fundamentally linear thinking in an essentially non-linear world.
Keywords: Business & Economics / Development / Business Development; Business & Economics / Development / Economic Development; Business & Economics / Economic History; Business & Economics / Economics / General; Philosophy / General; Science / System Theory; Social Science / Developing & Emerging Countries